Spectrum management for 5G: assignment methods for spectrum sharing - Fernando Beltrán; Maria Massaro (International Telecommunications Society (ITS), 2018)
The current development of fifth generation of mobile communications technology, known as 5G, has triggered intense discussions about proper spectrum assignment procedures to accommodate 5G spectrum needs (LStelcom et al., 2017). In particular, spectrum scarcity and lengthy processes to remove and relocate low-intensity uses have led to a renewed interest in spectrum sharing (PCAST, 2012). Since access to radio spectrum for the provision of commercial mobile communications services, mostly cellular telephony and wireless broadband access, is generally granted by means of exclusive usage rights, a growing stream of research is recognising efficiency gains of allowing spectrum to be shared, questioning the primacy of exclusive access to spectrum (Beltran, 2017). Against this background, this paper aims to discuss recent international attempts to introduce some forms of spectrum sharing for the assignment of spectrum rights for the fourth generation (4G) of mobile communications technology, in the light of current challenges posed by the fifth generation (5G). Recently, three cases have called or are calling for the award of rights to the shared use of the spectrum. These cases reveal the rationales supporting National Regulatory Authorities' (NRAs) decisions that led or will lead to the assignment of shared spectrum rights. Furthermore, they also reveal specific assignment methods – either proposed or not fully deployed, which this paper uses for its main contribution. The three cases considered for the analysis are: the 800 MHz and 2.6 GHz bands auction planned by the UK regulator in 2013; the Licensed Shared Access (LSA) approach defined by the European Union (EU); and the 3.5 GHz ecosystem developed in the United States (US). Using an analytical framework for the identification of the adequate spectrum management approach, this paper undertakes a comparison of the abovementioned three cases to draw lessons applicable to the upcoming 5G services.
Keywords: 330